Demenageries : thinking (of) animals after Derrida - Berger, Anne-Emmanuelle, 1958-; Segarra, Marta (Critical studies (Amsterdam, Netherlands) ;, 2011)
Demenageries, Thinking (of) Animals after Derrida is a collection of essays on animality following Jacques Derrida's work. The Western philosophical tradition separated animals from men by excluding the former from everything that was considered "proper to man": laughing, suffering, mourning, and above all, thinking. The "animal" has traditionally been considered the absolute Other of humans. This radical otherness has served as the rationale for the domination, exploitation and slaughter of animals. What Derrida called " la pensée de l'animal " (which means both thinking concerning the animal.